2014
DOI: 10.3390/s140711672
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Pyrogenicity and Cytotoxicity Profiles of Flex Sensors to be Used to Sense Human Joint Postures

Abstract: Flex sensors can be usefully adopted as mechanical-electrical transducers to measure human joint movements, since their electrical resistance varies proportionally to the angle assumed by the joint under measure. Over time, these sensors have been investigated in terms of mechanical and electrical behavior, but no reports have detailed the possibility of their adoption not just on top but under the human skin of the joint. To this aim, our work investigated in vitro the pyrogenic potential and cytotoxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…1) based on acquired experiences for nonsurgical purposes. [14][15][16][17][18] The glove was equipped with 14 flex sensors (by Flexpoint Sensor Systems, Inc., Draper, UT) and a 3-axis accelerometer (ADXL335, by Analog Devices, Inc., Norwood, MA) able to measure the flex/ extension capabilities of the finger joints of a human hand, plus the wrist movements. Flex sensors were placed on distal interphalangeal, proximal interphalangeal, and metacarpophalangeal finger joints, and the accelerometer was placed on backside of the hand (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1) based on acquired experiences for nonsurgical purposes. [14][15][16][17][18] The glove was equipped with 14 flex sensors (by Flexpoint Sensor Systems, Inc., Draper, UT) and a 3-axis accelerometer (ADXL335, by Analog Devices, Inc., Norwood, MA) able to measure the flex/ extension capabilities of the finger joints of a human hand, plus the wrist movements. Flex sensors were placed on distal interphalangeal, proximal interphalangeal, and metacarpophalangeal finger joints, and the accelerometer was placed on backside of the hand (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, permanent or semipermanent insertion can provide a better quality of life for those who have experienced severe physical trauma, when it is mandatory to record a stream of data from particular joints so as to continuously monitor reduced motor activities, and/or to drive electromechanical prosthesis. Only one work has addressed this problem, performing in vitro analysis, and it was demonstrated that only specific RFSs (polyimideencapsulated ones) can be potentially used for this purpose because they showed low pyrogenic effects, with no relevant cytotoxicity, and displayed a low proinflammatory profile [96].…”
Section: Physico-biochemical Characteristicsmentioning
confidence: 99%
“…Flex sensors are also used in gloves [ 39 ] to recognize sign language and health monitoring systems to measure the angle and motion of muscle joints [ 40 ]. Recently, flex sensors have been used in wearable technology for conducting real-time monitoring in the everyday environment [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%